2019
DOI: 10.1101/715276
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EEG and fMRI Evidence for Autobiographical Memory Reactivation in Empathy

Abstract: Empathy relies on the ability to mirror and to explicitly infer others' inner states. Studies on healthy populations show consistent evidence supporting the idea that our memories play a role in empathy when building a representation of others' inner states (Buckner & Carroll, 2007a; Spreng & Grady, 2009a;Spreng, Mar, & Kim, 2009). However, direct evidence of a reactivation of autobiographical memories (AM) when it comes to empathizing with others' inner states is yet to be shown. To address this question, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 93 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…43 For that reason, the use of cluster-based non-parametric permutation methods is widespread, not only in fMRI [44][45][46][47] but more recently also in M/EEG studies. [48][49][50][51] In our study, a nonparametric cluster-based permutation approach, proposed in 43 for fMRI data, was adapted and implemented for the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…43 For that reason, the use of cluster-based non-parametric permutation methods is widespread, not only in fMRI [44][45][46][47] but more recently also in M/EEG studies. [48][49][50][51] In our study, a nonparametric cluster-based permutation approach, proposed in 43 for fMRI data, was adapted and implemented for the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work suggested that the hippocampus may be spontaneously recruited when thinking about others' social pain (e.g., others' suffering arising from social rejection, grief, or other psychological pain; Immordino-Yang & Singh, 2013 see also Perhs, Zaki, Taruffi, Kuchinke, & Koelsch, 2018) and that sharing painful and similar experiences with other people increases trust, empathic concern, and cooperation (e.g., Bastian, Jetten, & Ferris, 2014;Hodges, Kiel, Kramer, Veach, & Villanueva, 2010). Newer developing research is emerging that directly investigates the reactivation of memory online during empathy for pain tasks, revealing that empathy for others' pain increases when people reported that they recalled a related autobiographical memory as well as it's neural basis (Meconi et al, 2019;Wagner, Rutgen, & Lamm, 2019). For example, Wagner et al provide some preliminary evidence that increased pattern similarity between fist-hand pain experience and empathy for others' pain within the hippocampus, TPJ, retrosplenial cortex, and anterior insula.…”
Section: An Effect Of Episodic Representation and Mentalizing On Socimentioning
confidence: 99%
“…43 For that reason, the use of cluster-based non-parametric permutation methods is widespread, not only in fMRI [44][45][46][47] but more recently also in M/EEG studies. [48][49][50][51] In our study, a nonparametric cluster-based permutation approach, proposed in 43 for fMRI data, was adapted and implemented for the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%